Board busyness and corporate payout: are all busy directors the same?. (3rd January 2022) - Benson, Bradley; Davidson, Travis; James, Hui; Wang, Hongxia
Abstract: We investigate how board busyness affects corporate payout policies. We find that board busyness increases the propensity and the level of cash distribution to shareholders. The likelihood and the level of share repurchases increase with inside director busyness, while the propensity to pay dividends and the level of dividends increase with independent director busyness. Further analysis shows that SOX and the Jobs and Growth Tax Relief Reconciliation Act do not alter the positive association between busy independent directors and the likelihood of paying dividends, nor do these regulations change busy inside directors' preference for repurchases.